Mengintegrasikan Keunggulan Operasional dan Orientasi Pasar: Kerangka Konseptual untuk Meningkatkan Kinerja Organisasi - Hartoyo, Hartoyo (Awatara Publisher, 2025)
This conceptual paper explores the integration of operational excellence and market orientation as complementary drivers of organizational performance. Operational excellence emphasizes efficiency, reliability, and continuous improvement, while market orientation focuses on responsiveness, customer value creation, and external adaptability. Although these constructs have traditionally been studied separately, their integration provides a more comprehensive understanding of how organizations can sustain competitive advantage. Drawing upon dynamic capabilities, ambidexterity, and resource-based perspectives, the study develops a conceptual framework that highlights the synergies between efficiency and responsiveness. The results reveal that operational excellence strengthens a firm’s ability to reconfigure processes, while market orientation enhances sensing and seizing of opportunities. Together, they form higher-order capabilities that enable resilience in dynamic environments. The framework also emphasizes the role of leadership, organizational culture, and cross-functional collaboration in achieving effective integration. Additionally, the study highlights potential tensions, such as rigidity from excessive efficiency or inefficiency from excessive responsiveness, and proposes strategies to balance them. The paper contributes theoretically by synthesizing fragmented literature streams and offering testable propositions for future research. From a managerial standpoint, it provides guidance for embedding customer intelligence into operations and aligning performance metrics with both efficiency and market responsiveness. The findings underline integration as a critical frontier in management scholarship and practice.